Investment Decisions Among Millennials and Generation Z: The Role of Education, Financial Literacy, and Instagram Content - Safitri, Ni Wayan Noviana; Saputri, Luh Gede Elvina Adi; Siagian, Reynaldo Angga (Universitas Pendidikan Nasional, 2025)
This research investigates how education level, financial literacy, and Instagram content influence investment decision-making among Millennials and Generation Z in Labuan Bajo. This study adopts a quantitative methodology, utilizing an online questionnaire that applies a five-point Likert scale to collect data. The population consists of Labuan Bajo residents belonging to the Millennial and Z generations. The sample was selected using purposive sampling, targeting respondents who had previously viewed Pegadaian’s Instagram content. From the 105 respondents who completed the questionnaire, only 74 individuals met the eligibility criteria and were included in the final sample. The results of the multiple linear regression analysis revealed that Instagram content (X3), financial literacy (X2), and education level (X1) each exert a positive and statistically significant effect on investment decision-making (Y). To encourage more knowledgeable and responsible investing behavior among younger people, these findings emphasize the need to raise educational attainment and financial literacy as well as using social media platforms to efficiently distribute information. The main implication of this study is the importance of integrating financial education with effective digital communication strategies to foster prudent investment behavior among youth. Furthermore, it highlights the potential of social media, when used appropriately, to serve as a strategic educational tool in enhancing public financial literacy.